Tuning the radial structure of core–shell silicon carbide nanowires. Issue 6 (2nd December 2014) - Negri, M.; Dhanabalan, S. C.; Attolini, G.; Lagonegro, P.; Campanini, M.; Bosi, M.; Fabbri, F.; Salviati, G.
Abstract : By varying the growth conditions in chemical vapour deposition synthesis we demonstrate the possible tuning of the core–shell ratio of SiC/SiO2 nanowires. Abstract : The influence of growth conditions on structural properties is reported for core–shell SiC/SiO2 nanowires grown on silicon substrates by a chemical vapour deposition (CVD) technique. Scanning Electron Microscopy (SEM) and Transmission Electron Microscopy (TEM) studies show a correlation between the growth temperature and the nanowire structure and highlight the possibility to control the inner core diameter by varying the precursor concentration. The nanowire covering of the substrate was considerably enhanced and homogenized using drop casting surfactant-aided deposition of catalysts on an H-terminated silicon 100 surface.